THE MAJORITY OF MYELINATED AND UNMYELINATED SENSORY NERVE FIBERS THAT INNERVATE BONE EXPRESS THE TROPOMYOSIN RECEPTOR KINASE A - Castañeda-Corral, Gabriela (2011)
Although skeletal pain is a leading cause of chronic pain and disability, relatively little is known about the specific populations of nerve fibers that innervate the skeleton. Recent studies have reported that therapies blocking nerve growth factor (NGF) or its cognate receptor, tropomyosin receptor kinase A (TrkA) are efficacious in attenuating skeletal pain. A potential factor to consider when assessing the analgesic efficacy of targeting NGF-TrkA signaling in a pain state is the fraction of NGF-responsive TrkA(+) nociceptors that innervate the tissue from which the pain is arising, as this innervation and the analgesic efficacy of targeting NGF-TrkA signaling may vary considerably from tissue to tissue. To explore this in the skeleton, tissue slices and whole mount preparations of the normal, adult mouse femur were analyzed using immunohistochemistry and confocal microscopy. Analysis of these preparations revealed that 80% of the unmyelinated/thinly myelinated sensory nerve fibers that express calcitonin gene-related peptide (CGRP) and innervate the periosteum, mineralized bone and bone marrow also express TrkA. Similarly, the majority of myelinated sensory nerve fibers that express neurofilament 200 kDa (NF200) which innervate the periosteum, mineralized bone and bone marrow also co-express TrkA. In the normal femur, the relative density of CGRP(+), NF200(+) and TrkA(+) sensory nerve fibers per unit volume is: periosteum > bone marrow > mineralized bone > cartilage with the respective relative densities being 100: 2: 0.1: 0. The observation that the majority of sensory nerve fibers innervating the skeleton express TrkA(+), may in part explain why therapies that block NGF/TrkA pathway are highly efficacious in attenuating skeletal pain.